2005
DOI: 10.1016/s0002-9440(10)62358-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Smad7 in Mouse Eyes Accelerates Healing of Corneal Tissue after Exposure to Alkali

Abstract: Damage to the cornea from chemical burns is a serious clinical problem that often leads to permanent visual impairment. Because transforming growth factor (TGF)-␤ has been implicated in the response to corneal injury, we evaluated the effects of altered TGF-␤ signaling in a corneal alkali burn model using mice treated topically with an adenovirus (Ad) expressing inhibitory Smad7 and mice with a targeted deletion of the TGF-␤/activin signaling mediator Smad3. Expression of exogenous Smad7 in burned corneal tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
134
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(144 citation statements)
references
References 69 publications
9
134
0
1
Order By: Relevance
“…Reduced inflammation and angiogenesis have also been reported in corneal wounds with exogenous Smad7 expression. 9 However, in contrast to that study, in which Smad7 was introduced to all cell types in the wound, Smad7 transgene expression in our current study was restricted to keratinocytes. Because NF-B signaling, the central mediator of inflammation, was reduced primarily in the epidermis of wounds from Smad7 tg mice (evidenced by reduced p50), this change could contribute significantly to reduced inflammatory cytokine production in keratinocytes.…”
Section: Stromal Effects Of Epithelial-specific Smad7 Overexpression mentioning
confidence: 66%
See 1 more Smart Citation
“…Reduced inflammation and angiogenesis have also been reported in corneal wounds with exogenous Smad7 expression. 9 However, in contrast to that study, in which Smad7 was introduced to all cell types in the wound, Smad7 transgene expression in our current study was restricted to keratinocytes. Because NF-B signaling, the central mediator of inflammation, was reduced primarily in the epidermis of wounds from Smad7 tg mice (evidenced by reduced p50), this change could contribute significantly to reduced inflammatory cytokine production in keratinocytes.…”
Section: Stromal Effects Of Epithelial-specific Smad7 Overexpression mentioning
confidence: 66%
“…8 Transient adenoviral gene transfer of Smad7, an antagonist of TGF␤ signaling, in corneal epithelium and stroma resulted in accelerated corneal wound healing with reduced inflammation. 9 Further, Smad7 gene transfer to the lens epithelium and stroma prevented injury-induced epithelial-mesenchymal transition of lens epithelial cells and suggests a potential role of Smad7 in prevention of capsular fibrosis. 10 However, adenoviral vector delivery of Smad7 to balloon-injured rat carotid arteries resulted in reduced vascular healing.…”
mentioning
confidence: 92%
“…[105][106][107] Our results show that in mice Smad7 gene introduction by topical application suppresses scarring and neovascularization of the burned cornea, restoring its transparency. 104 Smad7 also suppressed generation of myofibroblasts, macrophage invasion, and the expression of wound healing-related cytokines. The effects were more marked than those seen in Smad3-null mice, probably because Smad7 also suppresses phosphorylated RelA of the NF-kB pathway, which leads to suppression of inflammation cascades.…”
Section: Gene Therapy For the Treatment Of Corneal Inflammation And Fmentioning
confidence: 94%
“…Using a mouse corneal alkali burn model, we have shown that loss of Smad3 suppresses tissue destruction of the healing cornea in association with a reduction of macrophage infiltration, inhibition of myofibroblast generation, and suppression of growth factor expression. 104 Neovascularization also potentially impairs vision. Adenoviral gene transfer of mouse Smad7 cDNA has been used in the treatment of tissue fibrosis in several disease models, that is, bleomycin-induced pulmonary fibrosis, drug-induced liver fibrosis, or kidney fibrosis by unilateral ureteral obstruction.…”
Section: Gene Therapy For the Treatment Of Corneal Inflammation And Fmentioning
confidence: 99%
See 1 more Smart Citation